Nuclear Translocation of SRPKs Is Associated with 5-FU and Cisplatin Sensitivity in HeLa and T24 Cells - Sigala, Ioanna (Cells, 2021)
Serine/arginine protein kinases (SRPKs) phosphorylate Arg/Ser dipeptide-containing proteins that play crucial roles in a broad spectrum of basic cellular processes. The existence of a large internal spacer sequence that separates the bipartite kinase catalytic core and anchors the kinases in the cytoplasm is a unique structural feature of SRPKs. Here, we report that exposure of HeLa and T24 cells to DNA damage inducers triggers the nuclear translocation of SRPK1 and SRPK2. Furthermore, we show that nuclear SRPKs did not protect from, but on the contrary, mediated the cytotoxic effects of genotoxic agents, such as 5-fluorouracil (5-FU) and cisplatin. Confirming previous data showing that the kinase activity is essential for the entry of SRPKs into the nucleus, SRPIN340, a selective SRPK1/2 inhibitor, blocked the nuclear accumulation of the kinases, thus diminishing the cytotoxic effects of the drugs. ATR/ATM-dependent phosphorylation of threonine 326 and serine 408 in the spacer domain of SRPK1 was essential for the redistribution of the kinase to the nucleus. Substitution of either of these two residues to alanine or inhibition of ATR/ATM kinase activity abolished nuclear localization of SRPK1 and conferred tolerance to 5-FU treatment. These findings suggest that SRPKs may play an important role in linking cellular signaling to DNA damage in eukaryotic cells.